Korelasi Kalsium Darah dan Kalsium Susu pada Sapi Perah Laktasi Awal: Literatur Review - Dafa, Adji Muhammad; Hadiputra, Raafi Akbar; Ismail, Abiyyu Hassan; Putri, Liana; Nurrofingah, Ulfa; Nafisah, Ainun (Jurnal Sains Peternakan Nusantara, 2025)
Calcium plays a crucial role in maintaining physiological functions in dairy cows during early lactation, a period marked by a sharp increase in mineral demand for colostrum formation and milk production. Imbalances in calcium supply during this phase frequently lead to hypocalcemia, affecting health and milk yield. A review of recent literature indicates a strong association between blood calcium concentration and milk calcium levels, where fluctuations in blood calcium tend to correspond with changes in calcium secreted into milk. Previous studies reported a high positive correlation, with a value of 0.905, demonstrating a close relationship between these two variables. Physiological mechanisms involving parathyroid hormone, vitamin D, and bone mobilization play major roles in regulating calcium homeostasis during this critical period. Monitoring both blood and milk calcium serves as an important indicator of metabolic status and supports the development of effective mineral supplementation strategies for transition dairy cows